AKIBAT HUKUM PENYALAHGUNAAN KEADAAN DALAM PERJANJIAN JUAL BELI TANAH DAN BANGUNAN - Rezky Muharjo; Habib Adjie (Res Judicata, 2019)
Problems that often occur in making contracts are the presence of one party who is in a strong economic position and seeks to gain dominance over the other party resulting in misuse of the situation (misbruik van omstandigheden) which is one example found in the Decision of the Supreme Court of the Republic of Indonesia No. 3182 K / PDT / 2010. The author in this study wants to examine and analyze further the legal basis of abuse of circumstances in the law of engagement in Indonesia and the ratio decidendi of the Decision of the Supreme Court of the Republic of Indonesia No. 3182 K / PDT / 2010. The research method used is normative legal research, namely legal research conducted by examining library materials or secondary legal materials while the problem approach is done using the law approach, conceptual approach and case approach. The results of the study indicate that the teachings of misuse of the state (misbruand van omstandigheden) in Indonesia cannot be found in the Law, but have been accepted in jurisprudence as a fourth form of disability. On the Decision of the Supreme Court of the Republic of Indonesia Number 3182 K / PDT / 2010 there are two elements of misuse of the situation as a basis for judges, namely strong parties can impose their will on weak parties, so that weak parties follow the terms of the contracts submitted to them and power it is used to impose the will so that it brings benefits to it so that it is contrary to fair rules.